Surgical treatment of the osteoporotic spine with bone cement-injectable cannulated pedicle screw fixation: technical description and preliminary application in 43 patients (Clinics, 2015)
OBJECTIVES: To describe a new approach for the application of polymethylmethacrylate augmentation of bone cement-injectable cannulated pedicle screws. METHODS: Between June 2010 and February 2013, 43 patients with degenerative spinal disease and osteoporosis (T-score